Evaluation of The Proposed Strategy for the Iraqi Media Network For The Period (2024-2028), Field Research - Alhamdani, Aous; Abdullah, Yousif; Umar, Muhammad (Journal of Economics and Administrative Sciences, 2024)
The current research aims to study a crucial phase of strategic management, which is strategic evaluation, to assess the proposed strategy through data analysis, ensuring its implementation with minimal deviation from the planned course. The research focuses on studying and evaluating the proposed strategy for the Iraqi media network for the years 2024-2028, examining its effectiveness and alignment with the state's directions. This involves understanding the realism of strategic visions, plans, and programs and building a suitable conceptualization.The research takes into consideration the environmental conditions and relies on scientific principles and steps to formulate a comprehensive and realistic strategy. The study sample consists of senior leaders, including general managers and experts in the Iraqi media network, totaling 15 individuals selected purposefully to ensure choosing experts most relevant to the strategy, responsible for its implementation.The research hypothesis suggests a consensus among the network's managers and experts on the proposed strategy for the next five years in all its dimensions. The research results indicate that the reality of plans, programs, and visions is very good, developed by experienced leaders capable of evaluating the proposed strategy. The findings also demonstrate a clear acceptance of the strategy by the research sample and alignment with the proposed strategic alternative.